Research on the evaluation index system for happy rivers and lakes: a case study of Xinchang County in Zhejiang Province, China - Li, Xiaoyu; Cui, Chenxi; Shui, Bonian; Hu, Chengye; Ye, Zhou; Zhang, Yong (Frontiers in Ecology and Evolution, 2024)
The “Happy Rivers and Lakes” initiative is an important measure to systematically address the complex water issues in China. It further highlights the effectiveness of constructing happy rivers and lakes based on river health assessments. This approach aims to identify typical practices and the effectiveness of river and lake management and protection at the local level, guiding for river and lake management and conservation work in the new era. This study focuses on county-level administrative units and develops a research framework for the evaluation index system of happy rivers and lakes. A total of 11 primary indicators and 22 secondary indicators are selected from aspects such as river and lake safety, water resources, water environment, biodiversity, and social services. The evaluation and analysis are conducted around the Chengtan River, Huangze River, and Xinchang River, as well as two large reservoirs in Xinchang County. The results show that the comprehensive evaluation score of happy rivers and lakes in Xinchang County is 92.66, categorizing it as a model of happy rivers and lakes. The evaluation results aim to provide references and guidance for similar regions inside and outside Zhejiang Province in their research and practical applications related to happy rivers and lakes.